THU0578 Patients and physician related outcomes improve significantly over 12 months follow up in patients with juvenile systemic sclerosis. results from the juvenile scleroderma inception cohort. www.juvenile-scleroderma.com. (12th June 2018) - Foeldvari, I.; Klotsche, J.; Terreri, M.T.; Katsikas, M.; Stanevicha, V.; Avcin, T.; Cimaz, R.; Kostic, M.; Sifuentes-Giraldo, W.-A.; Sztajnbok, F.; Anton, J.; Nemcova, D.; et al.
Abstract : Background: Juvenile systemic scleroderma (jSSc) is an orphan disease with an estimated prevalence of around 3 per 1 000 000 children. There are no studies which evaluated prospectively the patient related outcomes in these patients. We report the data from juvenile scleroderma inception cohort (jSSc) regarding organ involvement and patient related outcomes. Methods: The jSSc is a prospective cohort of jSSc patients. Patients were enrolled who were diagnosed with jSSc, had a jSSc onset age under 16 years and were younger as age of 18 years at the time of inclusion. The patients are prospectively assessed every 6 months according to a standardised protocol. Patients with available 12 months follow up data were included in the analyses. Results: Currently 100 patients are followed in the jSSc cohort. 51 of them had available 12 months follow up data. Among those patients 37 (72.5%) had diffuse and 14 (27.5%) limited subtype. Mean age of onset of disease was 9.5 (±4.1) years and the mean disease duration at time of inclusion was 3.1 years (±3.2). The proportion of patients treated with DMARD increased from 74.5% to 88% at 12 months follow up. 86% were ANA positive at both assessments. Anti-scl70 positivity increased from 38% to 42%. Anticentromere antibody positivity was 2.4% at both assessments. Mean modified skin score decreased from 17.7 to 14.3 (p=0.151) Raynaud phenomenon occurred in 86% at enrolment and increased up to 88% at 12 months follow up. Nailfold capillary changes occurred around 70% at both assessments, but number of patients with active ulceration decreased from 28% to 16% (p=0.148). The number of patients with decreased FVC (FVC under 80%) decreased from 40.5% to 32% (p=0.497). The number of patients with pulmonary hypertension remained around 10%. No renal crisis or hypertension were reported. The gastrointestinal involvement was around 40% at both assessments. The number of patients with swollen joints decreased from 24% to 10% (p=0.06). The number of patients with muscle weakness decreased significantly from 33% to 9% (p=0.016), parallel to the number of patients with elevated CK values which decreased from 27% to 12% (p=0.074). All patient related outcomes, like global disease activity (p=0.048), global disease damage (p=0.05), Raynaud activity (p=0.003) and ulceration activity (p=0.001) improved significantly over 12 months. Physician assessed global disease activity (p=0.003) and ulceration activity (p=0.001) also improved significantly. Conclusions: Our data show, that jSSc patients over a 12 months disease course stayed quite stable or improved regarding organ involvement. But patient and physician related outcomes regarding activity assessment improved significantly. Disclosure of Interest: None declared